Keragaman Jenis Kupu-Kupu Superfamili Papilionoidae di Hutan Desa Kampung Ubadari, Fakfak dan Sekitarnya - Evie Lilly Warikar (Igya ser hanjop: Jurnal Pembangunan Berkelanjutan, 2021)
Tanah Papua is known to harbor high number of species richness and endemism, both in terrestrial and marine ecosystems. It stretches from snow-capped mountains to most-pristine coral reefs. However, with the improvement of social-economic and accessibility, infrastructure development has been accelerated in last decades. On one hand infrastructure development and improving social-economic are welcome, but without proper planning these progress can spoil the development and certainly ecosystems itself. It is known that many development that require conservation of natural ecosystems or forests are done with very limited data. Even for planning at the smallest management units, such as hutan desa, often have been done without sound data. This survey was designed to document Papilionidaer richness and potential in forests in Kampung Ubadari and its surrounding, Fakfak. Butterfly was observed randomly in the forests and openings in and around Kampung Ubadari, for 9 days from 08:00-16:00. About 103 species from 5 families were recorded during this observation. Nymphalidae with 45 species is the highest. Two endemic species Mycalesis pernotata andHarsiesis yolanthe are endemic New Guinea , which rare elsewhere, but recorded abundantly these forests and one protected species Ornithopther priamus.